Education in the Direction of Public-Private Partnership - Norma Suely Siqueira Eiras (Universidade Estadual Paulista Júlio de Mesquita Filho, 2008)
The process of the neoliberalism reveals, at its more intense moment, the submission of all the levels of the life human being the mercantile transactions, the capitalist inclination to the world-wide trading. In this manner, the neoliberal proposals objectify, over all, the creation of an only feeling to guarantee the success of its ideals of globalization, free-economy and State minimum, not inhibit the social politics, but partnership of the market. Amongst the artifices used for the neoliberal proposers, placed the Public-Private Partnerships (PPPs) with which this article concerns. From the conceptualization and characterization of the instrument Public-Private Partnerships (PPPs), national and European projects, developed through the PPPs, had been analyzed. The subjects of these projects involve Technology of Computer science and Communication and eLearning (education + technology + in the distance). Reflections had evidenced that the partnerships between governments and multinationals companies can lead to a loss of control on the part of the State on the educational formation of the citizens and the loss of identity of its resumes. The explanation for this phenomenon happens of the trend to the globalization. On the other hand, these partnerships bring profits politicians to the governments and economic to the companies.